A Study on Thermal Comfort of Walking Trails in Urban Mountain Parks: A Case Study of Gongchen Mountain in Lin’an - Wang, Meng (Scientific Journal of Technology, 2026)
With the intensification of the urban heat island effect, outdoor thermal comfort for residents has declined, making urban mountain parks a crucial refuge for seeking thermal relief during summer. Consequently, exploring strategies to regulate their thermal environment is urgent. As the core structural element of mountain parks, trail thermal comfort is significantly influenced by environmental factors such as slope gradient and aspect. However, current research on trail thermal comfort is predominantly focused on flat terrain, lacking in-depth exploration of complex micro-topographic factors. Taking Gongchen Mountain in Lin’an District, Hangzhou City, as a case study, this research combines summer meteorological data with ENVI-met simulations to investigate the impact of varying slopes and aspects on trail thermal comfort. The results indicate that the mountain’s aspect and slope gradient have a significant influence on the solar radiation received by trails, thereby affecting visitors’ thermal comfort perception. This study provides a theoretical foundation for the planning of urban mountain parks and climate-adaptive design, particularly for optimizing trail thermal comfort under complex topographical conditions.